Behavioral economics strategies for promoting adherence to treatment in heart failure patients. (14th October 2021) - Lipatova, T; Malinova, L; Eremin, A
Abstract: : Heart failure (HF) is characterized by an increased risk of both fatal and nonfatal adverse cardiovascular events, which required life-long and costly treatment. At the same time every cardiology practitioner is well aware, that despite huge efforts on patient's education there remains a substantial part of patients who do not always make rational choices regarding their treatment. Patient's knowledge does not always translate into adherence, so we must find ways to minimize the intent-behavior gap to improve the efficacy of HF treatment. We presume that behavioral economics can provide us with tools that will promote positive present behavior of patients. The purpose of the study was to examine the utility of behavioral economics-related concepts in understanding long-term treatment strategy in heart failure patients and acute heart failure survivors. Methods: We performed an open prospective study involving male patients with both chronic and acute heart failure (CHF n=65 and AHF n=54). Involved patients were surveyed on symptom severity, behavioral economics "parameters". Cognitive complexity was measured via "real life" case simulations. We assessed stress and depression with HADS and Zung's scales serially: on admission, 3d day of hospitalization and day before discharge. In patients with AHF, first assessment was performed after clinical stabilization. The primary outcomes were set as an adherence to prescribed medication assessed 6 and 36 months after discharge, rehospitalization due to cardiovascular reasons and self-assessed well-being. Results: We observed opposite patterns of stress dynamics in CHF and AHF groups. AHF patients demonstrated significant reduction of stress level on the 3d day since admission: 9.0 (7.1; 9.9) vs 6.4 (5.7; 7.4) units, p=0.037, with further increase at discharge, while in CHF patients there was tendency to significant change in parameter was absent. Patients who survived AHF demonstrated higher 6 month adherence to prescribed medication (62.9% vs 49.2%, p=0.047), at the same time there was the strong positive correlation between medication's price and self-induced therapy interruption (R=0.74, p<0.05). Both AHF and CHF reported financial planning as the major contributor for decision making in "real life" cases. Surprisingly in study population self-assessed well-being did not correlated with rehospitalization rate. Parameters that were significantly associated with CV rehospitalization included symptoms at admission (OR 2.1 CI 1.4; 3.2, p=0.002), regularly saving money (OR =2.7 CI 1.9; 4.6, p=0.001) and stress level at discharge (OR 1.6 CI 1.1; 2.4, p=0.027). Conclusion: Received results may be useful to identify heart failure patients at higher risk of self-induced treatment interruption. These patients could be offered focused support and counseling designed to enhance adherence to prescribed medication in order to improve long-term heart failure outcomes. Funding Acknowledgement: Type of funding sources: None.